2023
DOI: 10.1186/s13018-023-03710-y
|View full text |Cite
|
Sign up to set email alerts
|

Aspirin prevents estrogen deficiency-induced bone loss by inhibiting osteoclastogenesis and promoting osteogenesis

Abstract: Background Aspirin is a commonly used antipyretic, analgesic, and anti-inflammatory drug. Numerous researches have demonstrated that aspirin exerts multiple biological effects on bone metabolism. However, its spatiotemporal roles remain controversial according to the specific therapeutic doses used for different clinical conditions, and the detailed mechanisms have not been fully elucidated. Hence, in the present study, we aimed to identify the dual effects of different aspirin dosages on osteo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…175 The anti-inflammatory mechanism of aspirin is that it inactivates cyclooxygenase (COX), thereby inhibiting the conversion of free arachidonic acid oil into prostaglandins. 176 In the field of oral medicine, aspirin is used to treat periodontitis. 177 Therefore, the aspirin modification of PEEK surfaces can effectively inhibit the inflammatory response around bone implants.…”
Section: Synthetic Drug Coatingsmentioning
confidence: 99%
See 1 more Smart Citation
“…175 The anti-inflammatory mechanism of aspirin is that it inactivates cyclooxygenase (COX), thereby inhibiting the conversion of free arachidonic acid oil into prostaglandins. 176 In the field of oral medicine, aspirin is used to treat periodontitis. 177 Therefore, the aspirin modification of PEEK surfaces can effectively inhibit the inflammatory response around bone implants.…”
Section: Synthetic Drug Coatingsmentioning
confidence: 99%
“…NSAIDs have anti-inflammatory, antirheumatic, analgesic, and antipyretic effects. , Aspirin is widely used in the treatment of osteomyelitis, osteoarthritis, and various painful conditions . The anti-inflammatory mechanism of aspirin is that it inactivates cyclooxygenase (COX), thereby inhibiting the conversion of free arachidonic acid oil into prostaglandins . In the field of oral medicine, aspirin is used to treat periodontitis .…”
Section: Surface Modification Substance Coatingsmentioning
confidence: 99%
“…Molecular docking studies provide a more intuitive explanation of the interaction between AC and its predicted protein targets in relation to OP [16]. Docking analysis demonstrated that all eight major proteins are targets of AC in osteoporosis.…”
Section: Docking Calculationmentioning
confidence: 99%